Sintesis dan Karakterisasi Solid Polymer Electrolyte (SPE) Berbasis Nanofiber Selulosa untuk Menunjang Baterai Litium Berdensitas Tinggi dan Ramah Lingkungan - Muckharom, Ahmad Ali; Adithia, Rizky Putra; Karimah, Putri Diah Wahyu; Ditalistya, Tabah; Nuryanto, Rahmad; Efiyanti, Lisa (Universitas Andalas, 2024)
Lithium battery as one of the energy storage has two important elements, namely electrodes and electrolyte. Electrolyte is a part of the battery element that has undergone many developments. In this study, the manufacture of electrolytes in the form of Solid Polymer Electrolyte (SPE) was carried out by utilizing the abundant availability of nata de coco. The nanofibrous cellulose structure in Bacterial Cellulose (BC) nata de coco has the advantages of good porosity, flexibility in surface functionality, compact porous structure that provides abundant ion pathways and hetero atoms (oxygen atoms) with free electron pairs that facilitate ionic conduction. The SPE synthesis process was carried out by varying the soaking time of nata de coco in ethanol, namely 1, 2 and 3 days to determine the structure with optimal results. FTIR characterization results show the synthesis of cellulose nanofiber has the same groups as commercial cellulose groups in the form of O-H, C-H, C=O and C-O. CV characterization results show the SPE electrolyte has good redox properties, especially in the 2-day variation with the highest specific capacitance. The EIS test showed the lowest resistance in the 1-day variation sample with a conductivity of 0.017 ohm-1.